Role of Cholinergic Innervation and RGS2 in Atrial Arrhythmia - JONES, DOUGLAS L.; Tuomi, Jari M.; Chidiac, Peter (Frontiers in Physiology, 2012)
The heart receives both sympathetic and parasympathetic efferent innervation as well as having the ability to process information internally via an intrinsic cardiac autonomic nervous system (ICANS). For over a century, the role of the parasympathetic innervation via vagal acetylcholine release was related to controlling the tone primarily via heart rate. Although subsequently in the late 1800’s, shown to play a role in atrial arrhythmia, the myocardium took precedence from the mid-1950s until a resurgence of interest in the autonomics in the last decade. Originally ignored as being benign and thus left untreated, recent emphasis has focused on atrial arrhythmia as atrial fibrillation is the most common arrhythmia seen by the general practitioner. It is now recognized to have significant mortality and morbidity due to resultant stroke and heart failure, and with the aging population, there will be an unprecedented increased burden on health care resources. Although it has been known for more than half a century that cholinergic stimulation can initiate atrial fibrillation, the classical concept focused on the M2 receptor and its signalling cascade including RGS4, as these had been shown to have predominant effects on nodal function (heart rate and conduction block) as well as contractility. However, recent evidence suggests that the M3 receptor may have a major role in initiation and perpetuation of atrial fibrillation and RGS2, a putative regulator of the M3 receptor, may be a target for therapeutic intervention. Mice lacking RGS2 (RGS2-\-), were found to have significantly altered electrophysiological atrial responses and were more susceptible to electrically-induced atrial fibrillation. Vagally-induced or programmed stimulation-induced atrial fibrillation could also be blocked by the selective M3R antagonist, darifenacin. These results suggest a potential surgical target (ICANS) and pharmacological targets (M3R, RGS2) for the management of atrial fibrillation